Strategi Penerapan Budaya Keamanan Pangan pada Rantai Pasok Distribusi di PT XYZ - Wilis, Nabila Sekar; Dewanti-Hariyadi, Ratih; Sartika, Ratu Ayu Dewi (Jurnal Teknologi dan Industri Pangan, 2025)
Food safety culture (FSC) can be defined as how a group or organization of individuals achieve food safety in their thoughts and behaviors. Extending FSC implementation to downstream industries can assure quality and safety in the food supply chain. However, food distributors often lack a thorough understanding of good warehouse practices (GWP) and good distribution practices (GDP), even though both are essential to ensure the quality and safety of food. The inspection report by Indonesian Food and Drug Authority (Badan Pengawas Obat dan Makanan – BPOM) from 2017−2021, more than 30% of distribution facilities did not conform to the standard. This study evaluated employees' perception of FSC, analyze the Strengths, Weaknesses, Opportunities, and Threats of FSC implementation, and develop strategies for implementation in a food distribution company (PT XYZ). The research employed quantitative and qualitative methods. The quantitative study involved a questionnaire completed by 350 respondents, revealing that 82.13% of the employees perceived a positive perception of FSC. Meanwhile, the qualitative study included a focus group discussion with 21 informants, that identified key weaknesses and threats to FCS implementation. The Internal Factor Evaluation−External Factor Evaluation (IFE−EFE) analysis identified seven strengths, 11 weaknesses, seven opportunities, eight threats, and nine alternative strategies for the implementation of food safety culture at PT XYZ. The strategy with the highest total attractive score (TAS) of 6.91, based on quantitative strategic planning matrix (QSPM), was the periodic implementation of “Gemba program” to monitor food safety practices.